Extensive coral mortality and critical habitat loss following dredging and their association with remotely-sensed sediment plumes. (August 2019) - Cunning, Ross; Silverstein, Rachel N.; Barnes, Brian B.; Baker, Andrew C.
Abstract: Dredging poses a potential threat to coral reefs, yet quantifying impacts is often difficult due to the large spatial footprint of potential effects and co-occurrence of other disturbances. Here we analyzed in situ monitoring data and remotely-sensed sediment plumes to assess impacts of the 2013–2015 Port of Miami dredging on corals and reef habitat. To control for contemporaneous bleaching and disease, we analyzed the spatial distribution of impacts in relation to the dredged channel. Areas closer to dredging experienced higher sediment trap accumulation, benthic sediment cover, coral burial, and coral mortality, and our spatial analyses indicate that >560, 000 corals were killed within 0.5 km, with impacts likely extending over 5–10 km. The occurrence of sediment plumes explained 60% of spatial variability in measured impacts, suggesting that remotely-sensed plumes, when properly calibrated against in situ monitoring data, can reliably estimate the magnitude and extent of dredging impacts. Highlights: Sediment traps accumulated up to 830 kg of fine sediment per m 2 during dredging. Sediment covered 50–90% of adjacent reefs, remained elevated 10–100 × 2 yr later. >560, 000 corals within 0.5 km of the channel were lost due to dredging. Dredge plumes detected by satellite predict 60% of variability in benthic impacts. Dredging impacted corals and reef habitat at least 2.5 km and possibly >10 km away.